Oxygen changes crack modes of Ni-based single crystal superalloy. Issue 12 (2nd December 2021) - Li, Xueqiao; Liu, Yinong; Zhao, Yunsong; Chen, Yanhui; Li, Ang; Zhang, Jianfei; Zhai, Yadi; Li, Zhipeng; Ma, Dongfeng; Li, Xiaochen; Zhang, Qing; Yang, Xiaomeng; et al.
Abstract : Oxygen-affected cracking commonly presents on thin Ni-based single crystal superalloy components serving in high temperature and oxidizing environments. This study uses a newly developed in-situ thermal-stress environmental transmission electron microscope to investigate the oxidation and fracture behaviors of Ni-based single crystal superalloy at 650°C under stress. The in-situ oxidation was found to change the tensile fracture mode from the close-packed {111} planes of plastic fracture to { 001 } planes adjacent to γ/γ′ interfaces of brittle fracture. The microanalysis also revealed that the γ′ cuboids, γ phase, and γ/γ interface exhibit different oxidation behavior, thus underscoring the thickness debit effect. GRAPHICAL ABSTRACT: UF0001 IMPACT STATEMENT: This paper firstly time provides direct in-situ oxygen-affected cracking behavior.